Legal Autonomy of Women in Neonatal Healthcare Decision-Making: A Critical Analysis of Indian Laws and International Human Rights Norms - Prof. (Dr.) Sanjeet Singh, Dr. Sanjeev Kumar (Journal of Neonatal Surgery, 2025)
This paper discusses the legal autonomy of women in neonatal healthcare decision-making in India from the perspective of domestic legal frameworks and international human rights standards. The study interrogates the disjuncture between legal rhetoric and real-world impacts through textual analysis of constitutional provisions, legislative enactments, judicial precedents, and international instruments. The results demonstrate stark tensions between legacy patriarchal norms and burgeoning rights-consciousness, as most participants described significant barriers to women's decisional autonomy rooted in family authority structures, institutional inequities, and resource scarcity. Although formal provisions for autonomy are contained within both Constitutional guarantees and international obligations, implementation remains piecemeal. The paper concludes with recommendations for legal reforms, restructuring of institutions, and educational measures to enhance women's decisional capacity and emphasizes that respecting maternal autonomy extends beyond legal compliance to being a vital human rights practice in the context of neonatal care.